TiO2/Zeolite Coal Fly Ash Nanocomposite for Photodegradation of Naphthol Blue Black Dye: Optimization and Mechanism under Visible Light - Kusumawardani, Linda Jati; Syahputri, Yulian; Apriansyah, Apriansyah; Fathurrahman, Muhammad (Jurnal Kimia Valensi, 2025)
Naphthol Blue Black (NBB) is a water-insoluble synthetic azo dye with a molecular weight of 616.49 g/mol that requires alkaline treatment for solubility and poses environmental risks by reducing water quality, increasing BOD and COD, and disrupting aquatic ecosystems. The TiO₂/Zeolite Fly Ash nanocomposite represents a promising material for the photocatalytic degradation of NBB. Analysis of the TiO2/zeolite fly ash nanocomposites revealed the presence of Ti-O-Si and Ti-O-Al functional groups, along with a suitable band gap energy value of 2.85 eV for visible light consumption. The average particle size is 62-75 nm, with a relatively high crystallinity of 95.64%. The insertion of TiO2 into the surface of the zeolite changes the size of the catalyst from 62-75 nm to 10 nm and 98.2% crystallinity. An emphasis was placed on the key parameters governing the degradation process. The test results showed that the degree of degradation increases at lower pH, while changes in catalyst dosage and initial dye concentrations do not significantly affect the degradation of NBB. The addition of H2O2 demonstrates the increasing degradation efficiency. The optimum operating process was carried out by adding 1.2 % (v/v) of H2O2, the pH 2, 0.1% (w/v) of catalyst, an initial concentration NBB of 12 mg/l, and irradiating under visible light for 75 minutes. It was a short period to produce the best conditions for degrading 12 mg/l naphthol blue-black, with a degradation efficiency of 99.68%. The rate of photodegradation kinetics had a reaction rate constant of 0.0312 min-1 and was followed a pseudo-first-order Langmuir-Hinshelwood.  From the results, it was found that adsorption is an essential factor in the photodegradability of the dye. The linear transform of the Langmuir isotherm curve was further used to determine the characteristic parameters, which included the maximum absorbable dye quantity Qmax=11,8217 mgg-1. LC-MS/MS analysis identified the compounds formed through the photocatalytic degradation of naphthol blue-black dye into lower-molecular-weight molecules, such as benzoic acid, maleic acid, and phenol, which can gradually break down naturally into carbon dioxide and water.